The contest winner: Gifted or venturesome? - Marco Sahm (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper examines the chance of winning a Tullock-contest when participants differ in both their talent and their attitude towards risk. For the case of CARA preferences, it is shown that the winning probability may be higher for a low-skilled agent with a low degree of risk aversion than for a high-skilled agent with a high degree of risk-aversion. Such an outcome often is undesirable. It will occur if and only if the agents' ratio of degrees of risk aversion is larger than their ratio of skill levels and the rent of the contest is sufficiently high.
Keywords: C72; D72; 330; selection contest; asymmetric players; risk aversion; Nichtkooperatives Spiel; Risikoaversion; Public Choice; Theorie